The invasion of globalization to higher education: The critical discourse study of emancipated learning policy - Andi Muhammad Irawan; Iskandar Iskandar; Zul Afdal; Andi Muhammad Arif Haris; Warsidi Warsidi (Studies in English Language and Education, 2025)
This study employs Critical Discourse Analysis (CDA) to explore the argumentation strategies or Topoi analyses used to justify the importance of the Emancipated Learning Policy (Merdeka Belajar Kampus Merdeka/MBKM) in response to the globalization of education. The discourse of globalization of education around the world, including in Indonesia, has been a topic of growing concern that attracts researchers and academics. In the context of Indonesia, this country deserves a close look since globalization has shaped and reshaped the education policy and practices, as well as enforced the shift of higher education curriculum. Besides unfolding the argumentation strategies utilized by the government to legitimize the policy, the study sheds new light on an alternative analysis to comprehend the marketization of higher education in Indonesia. The topoi analysis was used to identify how globalization shapes the policy and how the national authority discursively justifies the claim of its importance. By analyzing topos of urgency utilized in policy texts and the ministers speech, the findings reveal that the presence of globalization invasion in the policy is evident, as identified in the following arguments, namely link and match, quick change, competitiveness, and collaboration. These findings convincingly show that the education policy and its implementation should be advanced to match the global values of globalization, which is expected to bring a positive impact to national education, especially in the higher education context.